The Notch signaling-regulated angiogenesis in rheumatoid arthritis: pathogenic mechanisms and therapeutic potentials - Zhao, Fang; He, Yini; Zhao, Zhihao; He, Jiarong; Huang, Hong; Ai, Kelong; Liu, Liang; Cai, Xiong (Frontiers in Immunology, 2023)
Angiogenesis plays a key role in the pathological process of inflammation and invasion of the synovium, and primarily drives the progression of rheumatoid arthritis (RA). Recent studies have demonstrated that the Notch signaling may represent a new therapeutic target of RA. Although the Notch signaling has been implicated in the M1 polarization of macrophages and the differentiation of lymphocytes, little is known about its role in angiogenesis in RA. In this review, we discourse the unique roles of stromal cells and adipokines in the angiogenic progression of RA, and investigate how epigenetic regulation of the Notch signaling influences angiogenesis in RA. We also discuss the interaction of the Notch-HIF signaling in RA's angiogenesis and the potential strategies targeting the Notch signaling to improve the treatment outcomes of RA. Taken together, we further suggest new insights into future research regarding the challenges in the therapeutic strategies of RA.